Application of Saline Infusion Sonocolpography in Diagnosis and Treatment of Perforated Transverse Vaginal Septum - Ayumi Ono; Iori Kisu; Tomoko Iijma; Hiroshi Senba; Kiyoko Matsuda; Motoko Katayama; Ayaka Iura; Yumiko Miura; Nobumaru Hirao (Case Reports in Obstetrics and Gynecology)
Transverse vaginal septum (TVS) is a particularly rare vaginal anomaly, and diagnosis is often difficult in a genital examination. We herein present a case of perforated TVS for which successful diagnosis and treatment were achieved using a new technique referred to as saline infusion sonocolpography. A 32-year-old female presented with primary infertility. Speculum examination revealed a blind vaginal canal with two pinpoint perforating holes. Foley catheters with inflated balloon were inserted into the two apertures, and then normal saline was injected through the catheters to distend the vaginal pouch. This procedure of saline infusion sonocolpography revealed the uterine cervix and vaginal pouch and permitted diagnosis of perforated TVS of the upper vagina. The septum was excised and a normal cervix was ascertained. The patient had no complication such as agglutination of the vagina postoperatively. This case suggests that saline infusion sonocolpography may be useful for diagnosis and treatment of TVS.